2006
DOI: 10.1007/s00281-006-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary auto-inflammatory disorders and biologics

Abstract: The term auto-inflammatory disorders has been coined to describe a group of conditions characterized by spontaneously relapsing and remitting bouts of systemic inflammation without apparent involvement of antigen-specific T cells or significant production of auto-antibodies. The hereditary periodic fever syndromes are considered as the prototypic auto-inflammatory diseases, and genetic studies have yielded important new insights into innate immunity. DNA analysis has greatly enhanced the clinical characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 78 publications
0
35
0
3
Order By: Relevance
“…A small study has shown the potential for use of methotrexate in resistant pseudogout, but the response was only noted ϳ2 months after initiation of therapy (6). Anakinra has been shown to be effective in treating the hereditary autoinflammatory conditions, which are characterized by the production of IL-1␤ due to increased inflammasome activity (7)(8)(9). Recently, the pathogenesis of crystal-induced arthropathy, including gout and pseudogout, was shown to mimic that of the hereditary autoinflammatory conditions (1,10).…”
Section: Discussionmentioning
confidence: 99%
“…A small study has shown the potential for use of methotrexate in resistant pseudogout, but the response was only noted ϳ2 months after initiation of therapy (6). Anakinra has been shown to be effective in treating the hereditary autoinflammatory conditions, which are characterized by the production of IL-1␤ due to increased inflammasome activity (7)(8)(9). Recently, the pathogenesis of crystal-induced arthropathy, including gout and pseudogout, was shown to mimic that of the hereditary autoinflammatory conditions (1,10).…”
Section: Discussionmentioning
confidence: 99%
“…After completing the study, the patient received a second 24-week treatment cycle, which was discontinued due to declining response. He experienced a flare similar to that with infliximab when subsequently treated with adalimumab 13 . The other 3 patients with flares associated with infliximab had been described in individual case reports 9,13 .…”
Section: Rheumatologymentioning
confidence: 99%
“…He experienced a flare similar to that with infliximab when subsequently treated with adalimumab 13 . The other 3 patients with flares associated with infliximab had been described in individual case reports 9,13 . Two patients responded favorably to anakinra after failing anti-TNF agents 19,20 , suggesting that interleukin 1 may play a role in the pathogenesis.…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…The response to anti-TNF-a drugs is variable, and there are reports of response to anakinra (a recombinant IL-1 receptor antagonist) [25,29].…”
Section: Traps: a Genetically Defined Heterogeneous Entitymentioning
confidence: 99%